Physical testing characteristics better explain draft outcome than in-game movement profile in junior elite Australian rules football players - Jennings, J.; Wundersitz, D. W.; Sullivan, C. J.; Cousins, S. D.; Tehan, G.; Kingsley, M. I. (Journal of Science and Medicine in Sport, 2021)
Objectives: The aim of this study was to investigate the extent to which Australian Football League (AFL) draft outcome is associated with physical performance and/or in-game movement profile. Design: Observational cohort design. Methods: Physical testing results and in-game global positioning system (GPS) data were collated from Victorian-based, draft-eligible participants in the under 18 boys NAB League competition (n = 450; age = 17.1 ± 0.3 y). Players were grouped by position as nomadic, fixed-position or fixed&ruck. Results: Individually, variables that best distinguish drafted and non-drafted players were: estimated VO2 max (all-position, nomadic, fixed&ruck: d = 0.60, 0.64, 0.53), standing vertical jump (d = 0.57, 0.58, 0.53), running vertical jump (d = 0.52, 0.51, 0.56), AFL agility (d = 0.49, 0.44, 0.67) and 20-m speed (all-position, nomadic: d = 0.50, 0.61). Factor analysis prior to binary logistic regression assessed the probability of factors influencing position-specific draft outcome. AFL agility (all-position, fixed&ruck: OR = 4.58, 15.86), anthropometry (all-position, nomadic, fixed, fixed&ruck: OR = 2.55, 2.06, 11.41, 7.99), and jumping (all-position, nomadic, fixed&ruck: OR = 1.75, 1.69, 2.68) were the factors most associated with positive draft outcome. More game involvement (fixed&ruck: OR = 2.22), sprinting (all-position, fixed&ruck: OR = 1.45, 2.06) and less non-sprinting activities (all-position, nomadic: OR = 0.64, 0.61) were associated with positive draft outcome. The fixed&ruck model was the best performing (X2(115) = 30.59, p < 0.001, AUC = 84.7%). Conclusions: Physical testing-related factors were most likely to influence draft outcome, where larger and more agile players were desirable draft picks. In-game movement profile had some bearing on draft outcome in all positional groups with the exception of fixed.